Distribution Moments and Equilibrium: Reply - Jean, William H. (Journal of Financial and Quantitative Analysis, 1972)
Unfortunately Professors Arditti and Levy (A-L) in their comment published in this issue of this journal did not realize that the determination of the investor optimum in my paper [1] was simultaneous with respect to the three parameters, the mean and the variance and the third moment of portfolio returns. When the nth moment was introduced, it was assumed that the investor chooses on the basis of all n parameters — the mean, second moment, third moment, etc. — through the nth moment.